(untitled) - Birnie, Patricia W. (Oxford, 1992)
This book is an attempt to assess the present state of international law concerning the protection of the world's natural environment. It does not seek to examine in detail all aspects of contemporary environmental problems, nor is it a work of policy analysis, but rather it aims to explore the basic principles, structure, and effectiveness of the international legal system as it relates to these issues. It is hoped that what emerges will provide the reader with a clearer and more coherent picture of the remarkable developments in international law which contemporary concern for the state of the global environment has brought about. This is the most comprehensive major treatment of the subject in English, by two authors with many years experience of teaching and writing in this field
Keywords: Environmental law, International,Luật môi trường, quốc tế